Epidermal Growth Factor Activates m-Calpain (Calpain II), at Least in Part, by Extracellular Signal-Regulated Kinase-Mediated Phosphorylation - Glading, A. (American Society for Microbiology, 2004)
How m-calpain is activated in cells has challenged investigators because in vitro activation requires near-millimolar calcium. Previously, we demonstrated that m-calpain activation by growth factors requires extracellular signal-regulated kinase (ERK); this enables tail deadhesion and allows productive motility. We now show that ERK directly phosphorylates and activates m-calpain both in vitro and in vivo. We identified serine 50 as required for epidermal growth factor (EGF)-induced calpain activation in vitro and in vivo. Replacing the serine with alanine limits activation by EGF and subsequent cell deadhesion and motility. A construct with the serine converted to glutamic acid displays constitutive activity in vivo; expression of an estrogen receptor fusion construct produces a tamoxifen-sensitive enzyme. Interestingly, EGF-induced m-calpain activation occurs in the absence of increased intracellular calcium levels; EGF triggers calpain even in the presence of intracellular calcium chelators and in calcium-free media. These data provide evidence that m-calpain can be activated through the ERK cascade via direct phosphorylation and that this activation may occur in the absence of cytosolic calcium fluxes.